Harrod's librarians' glossary - Prytherch, Ray (Gower Pub. AldershotGB, 2006)
Provides a guide to the terminology of the information handling industries, electronic storage and retrieval, networking, librarianship, bibliography, archive management, and the book trade both general and specialist.